Developing a New Operations Plan for the Bow River Basin Using Collaborative Modeling for Decision Support1. (13th May 2013) - Sheer, A. Michael S.; Nemeth, Michael W.; Sheer, Daniel P.; Van, Megan; Kelly, Michael; Hill, David; Lebherz, Samuel D.
Abstract The Bow River Basin is a cornerstone of Alberta's development. In 2010, stakeholders representing interests from agriculture, municipalities, environment, and more formed the Bow River Project Research Consortium to help determine the potential for improving the operations in the basin. At present, upstream reservoirs are operated primarily for hydropower, whereas downstream reservoirs are operated for irrigation. Through Collaborative Modeling for Decision Support the stakeholders were able to develop a new method for operating the system that would dramatically improve environmental performance. The main components of the new operating strategy called for: purchase or setting aside of a small amount of storage volume in the power reservoirs; a set of rules for releases from that storage; an agreement by the major irrigation districts with the largest water licenses to utilize their ability to shift deliveries to and from their large offstream storage reservoirs to allow for increased instream flows, and to allow junior water license holders (mainly municipal and industrial supplies) an uninterrupted water supply; limitations of reservoir fluctuations to improve inreservoir habitat for fisheries; and increased minimum flows throughout the system leading to improved environmental outcomes. Costs of this strategy were minimal, impacts on power revenue were estimated at <US$2 million/yr on average. Compensatory arrangements should be possible.